1996
DOI: 10.1093/toxsci/30.2.194
|View full text |Cite
|
Sign up to set email alerts
|

Species-Specific Recombinant Cell Lines as Bioassay Systems for the Detection of 2,3,7,8-Tetrachlorodibenzo-p-dioxin-like Chemicals

Abstract: which include polychlorinated biphenyls (PCBs), dibenzofuSpecies-Specific Recombinant Cell Lines as Bioassay Systems rans (PCDFs), and dibenzo-p-dioxins (PCDDs) as well as for the Detection of 2,3,7,8-Tetrachlorodibenzo-p-dioxin-like many other subclasses of PCDHs (Giesy et al., 1994a). These known to bioaccumulate and biomagnify in the food chain Exposure to specific polychlorinated diaromatic hydrocarbons (Ballschmitter et al., 1989; Tanabe et al., 1987; Webster and (PCDH), such as 2,3,7,8-tetrachlorodibenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
217
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(230 citation statements)
references
References 0 publications
13
217
0
Order By: Relevance
“…No induction in luciferase activity was observed when cells transfected with pT81 were treated with 5F 203 (1 mM) or TCDD (10 nM). Similar results were obtained when cells were transfected with a fragment of mouse native CYP1A1 promoter (inclusive of four dioxin responsive elements (DREs)) (pGudLuc1.1) (data not shown) (Garrison et al, 1996). When pTX.Dir-transfected cells were pretreated with an antagonist of AhR, a-naphthoflavone, before treatment with 5F 203, luciferase activity was reduced approximately 25%, suggesting competition between the two ligands for binding to the AhR (results not shown).…”
Section: Cyp1a1 and Cyp1b1 Inductionsupporting
confidence: 69%
“…No induction in luciferase activity was observed when cells transfected with pT81 were treated with 5F 203 (1 mM) or TCDD (10 nM). Similar results were obtained when cells were transfected with a fragment of mouse native CYP1A1 promoter (inclusive of four dioxin responsive elements (DREs)) (pGudLuc1.1) (data not shown) (Garrison et al, 1996). When pTX.Dir-transfected cells were pretreated with an antagonist of AhR, a-naphthoflavone, before treatment with 5F 203, luciferase activity was reduced approximately 25%, suggesting competition between the two ligands for binding to the AhR (results not shown).…”
Section: Cyp1a1 and Cyp1b1 Inductionsupporting
confidence: 69%
“…The chemically activated luciferase expression (CALUX) and chemically activated fluorescence expression (CAFLUX) cell bioassays are two state-of-the-art techniques that can be used to generate bioassay TEQ values (CA[F]LUX-TEQs) that can be compared with GC/HRMS TEQ estimates [23][24][25][26]. Both of these bioassays involve the use of genetically modified mouse hepatoma cells, and after exposure to sample extracts containing AhR ligands, they produce luciferase or enhanced green fluorescent protein, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Two independent observations confirm that the lipophilic mixtures isolated from breast milk act through this pathway. First, the DR-CALUX reporter assay, based on a synthetic promoter that detects Ah receptor ligands in a highly selective manner, [31] proves that the Ah receptor is activated following treatment with breast milk extracts. Second, we observed that the amplitude of CYP1A1 and CYP1B1 induction, determined by real-time RT-PCR, correlates with the total concentration PCDD/PCDF (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This rat hepatoma cell line carries a chromosomally integrated construct that drives expression of the firefly luciferase gene under control of a minimal promoter flanked by dioxin response elements. [31] The Ah receptor activation was monitored after 24 h treatments by measuring the luciferase activity in cell lysates. The results of this bioassay, expressed as 2,3,7,8-tetrachloro-dibenzop -dioxin (TCDD) equivalents in the lipid fraction, ranged from 73 pg/g in sample no.…”
Section: Analysis By Reporter Gene Assaymentioning
confidence: 99%